The Gambia : Joint Bank-Fund Debt Sustainability Analysis, 2018 Update - International Development Association; International Monetary Fund (World Bank, Washington, DC, 2018)
An updated debt sustainability analysis (DSA) indicates that The Gambia is currently in external debt distress and that public debt is unsustainable. Both external and domestic debt are very high, and a significant pipeline of already-contracted loans poses risks to solvency. External debt stock indicators have deteriorated since the March 2018 DSA, and all five external debt burden indicators breach their indicative thresholds by large margins and for an extended period in the passive scenario and in the active (baseline) scenario. The stress test results illustrate the country’s high vulnerability to shocks, total public debt is expected to remain elevated throughout the projection period, rollover risks associated with the short maturity of domestic debt are high, and contingent liabilities related to SOE debt pose additional risks. Furthermore, the sustained primary surpluses needed to reduce public debt would be politically and socially challenging given The Gambia’s substantial development needs. New borrowing would need to be on highly concessional terms and reserved for the very highest priority projects for which grant-financing is not available. The government should also refrain from offering any guarantees. An illustrative scenario shows how debt relief (comprising a deferral of principal due to pluri-lateral, bilateral official and private creditors and a softening of the terms of the already contracted loans)—complementing the implementation of a sound medium-term fiscal framework and debt strategy—could be instrumental in restoring debt sustainability.